The placebo response rate and nocebo events in obesity pharmacological trials. A systematic review and meta-analysis. (December 2022) - Chin, Yip Han; Ng, Cheng Han; Chew, Nicholas WS; Kong, Gwyneth; Lim, Wen Hui; Tan, Darren Jun Hao; Chan, Kai En; Tang, Ansel; Huang, Daniel Q; Chan, Mark Y; Figtree, Gemma; Wang, Jiong-Wei; et al.
Summary: Background: There is a growing number of trials examining the effectiveness of pharmacotherapies for obesity, however, little is known about placebo and nocebo effect in these trials. Hence, we sought to examine the effect of placebo in obesity trials, to better understand the potential factors affecting clinical endpoints in them. Methods: Medline, Embase, and Cochrane CENTRAL were searched for articles examining weight-loss RCTs examining patients with overweight or obesity in placebo-controlled arms from inception till 25 June 2022. This paper was registered online with PROSPERO (CRD42022302482). A single arm meta-analysis of proportions was used to estimate the primary outcomes, ≥5%, ≥10%, and ≥15% total weight loss – and the adverse effects that patients experienced during the trial. A meta-analysis of means was used to estimate the pooled mean differences of the secondary outcomes including, body weight measurements, lipid levels, glycemic indices, and blood pressure over time. Findings: A total of 63 papers involving 20, 454 patients and 69 trials were included. The proportion of patients that had ≥5%, ≥10%, and ≥15% weight loss was 20·4% (CI:16·1% to 25·0%), 8·3% (CI:6·1% to 10·9%), and 6·2% (CI:3·8% to 9·7%), respectively. Analysis by duration of trials showed stepwise increase in proportion of patients with ≥5% and ≥10% weight loss with increasing duration of study. Analysis of secondary outcomes found modest improvement in all analyses. The pooled average rate of overall AEs, serious AEs, and discontinuation was 73·7% (CI:68·0% to 79·0%), 3·4% (CI:2·4% to 4·5%), and 5·2% (CI:4·0% to 6·5%), respectively. In psychiatric complications, the pooled rates of anxiety and depression were 2·7% (CI:1·8% to 3·7%) and 2·5 (CI:1·7% to 3·3%). Interpretation: Our meta-analysis of placebo-treated participants in weight-loss RCTs indicate a significant placebo and nocebo effect. These findings are important to quantify their effect and may inform the design of future RCTs. Funding: This research did not receive additional support from organizations beyond the authors' academic institutions.